Waste Heat Recovery on a Liquefied Natural Gas Carrier with Tri-fuel Diesel Electric Propulsion using a Dual Loop Rankine Cycle - Lazaratou, Eleni (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ναυπηγών Μηχανολόγων Μηχανικών. Τομέας Ναυτικής Μηχανολογίας, 2015)
An estimated 20-50% of fuel energy in industrial processes is lost as waste heat. The large majority of this heat is rejected at low temperatures with an approximate 60% of industrial waste heat having a temperature below 230⁰C and an impressive 90% having a temperature below 316⁰C [13]. The high cost of fuel and growing concerns about the environment demand better utilization of this energy source. The present study examines waste heat recovery using an organic Rankine cycle (ORC), a thermodynamic cycle based on the classic steam-water Rankine cycle but adapted for exploitation of low-grade heat by replacing water with an organic compound. The class of organic compounds encompasses a large number of molecules, which contain atoms of carbon linked to other elements. The main benefit of using organic compounds is that their lower boiling points and critical properties allow for evaporation at lower temperatures than water, meaning lower temperature heat sources can be exploited. The goal of the present work is to apply ORC waste heat recovery technology to a marine propulsion system in order to improve the propulsion efficiency and reduce fuel consumption. ORC technology for waste heat recovery is not new with the first applications having been examined in the 1970s. However, it has only gained ground for marine applications in the past few years with the first system installed on a 75,000 GT large car/truck carrier in 2011 [1], [2]. The vessel to be examined in the present work is a 159,000 m3 liquefied natural gas (LNG) carrier with a triple-fuel diesel-electric propulsion system. The waste heat from the exhaust gas and the engine cooling water will be recovered using a dual loop Rankine system. Ultimately, it will be shown that the propulsion system efficiency can be improved by 2-7% while the fuel energy consumption to maintain a given speed can be reduced by 5-14.5%, depending on the speed. The analysis will begin with a review of the theoretical concepts behind the proposed system, which includes an overview of Rankine cycle basics in Chapter 2 and an analysis on organic fluids and their relevant properties in Chapter 3. Existing applications of ORC technology will be presented in Chapter 4. The propulsion system to be examined in the present work is described in detail in Chapter 5. The initial design parameters for the Rankine cycle application will be reviewed in Chapter 6. The simulation model, analytical approach and optimization problem to be used for the final system design will be presented in Chapter 7 and the results of the simulation will be included in Chapter 8. The results will be assessed from a techno-economic viewpoint in Chapter 9 and the final conclusions and suggestions for further research will be presented in Chapter 10.